2017
DOI: 10.1002/cjg2.30027
|View full text |Cite
|
Sign up to set email alerts
|

Stratified Crustal Anisotropy From Receiver Function and Its Particle Swarm Inversion

Abstract: Crustal anisotropy at multiple depths is essential for studying the vertical variation of crustal deformation. Due to the complexity of the crust, mapping the crustal anisotropy at different depth from teleseismic receiver function (RF) is an ongoing subject that requires further studies. Based on the previous works, this paper goes further to discuss the RF wavefield pattern of stratified crustal anisotropy by means of the generalized reflection and transmission coefficients method, which provides us a new th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…For stations with large difference between the two approaches (the difference in 𝜙 is greater than 15 ∘ , or that in 𝛿t is greater than 0.15 s), results from the P m s moveout fitting are used because we have found that this approach usually produces more stable results. This is mostly because the amplitudes of the P m s phase used by the second approach vary more significantly than the arrival times (Han et al, 2017). In addition, the significant trade-off between the crustal anisotropy, tilted axis of symmetry, and dipping interfaces may lead to variations in the stacking amplitude, making it difficult to reliably extract anisotropy using stacking amplitude.…”
Section: Measurement Of Single Layered Anisotropymentioning
confidence: 99%
“…For stations with large difference between the two approaches (the difference in 𝜙 is greater than 15 ∘ , or that in 𝛿t is greater than 0.15 s), results from the P m s moveout fitting are used because we have found that this approach usually produces more stable results. This is mostly because the amplitudes of the P m s phase used by the second approach vary more significantly than the arrival times (Han et al, 2017). In addition, the significant trade-off between the crustal anisotropy, tilted axis of symmetry, and dipping interfaces may lead to variations in the stacking amplitude, making it difficult to reliably extract anisotropy using stacking amplitude.…”
Section: Measurement Of Single Layered Anisotropymentioning
confidence: 99%